LINGUISTIC AND THEMATIC EXPLORATION OF WILLIAM CONGREVE'S THE WAY OF THE WORLD - Madhavi, P. Asha; Krishna, Kota Sai; Gundala, Upender (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study offers an in-depth analysis of the linguistic and thematic elements in William Congreve’s The Way of the World, focusing on how the play reflects social dynamics and power structures during the Restoration era. Using a qualitative approach that combines stylistic and comparative analysis, the research examines various aspects of the text, such as word choice, sentence structure, meaning, and rhetorical techniques. It explores how characters in the play use language as a tool for manipulation, deception, and negotiation in a society shaped by class, wealth, and marriage. The analysis highlights the complexity of Congreve’s dialogue, showing how witty exchanges and elaborate conversations represent the performative aspects of social interactions while subtly criticizing gender roles and societal expectations of the time. The research further connects these linguistic elements to key themes like power, gender, autonomy, and social manipulation, particularly focusing on how Congreve challenges traditional female roles through the character of Millamant, who seeks more equality in marriage. By comparing these themes to modern issues—such as contemporary feminist movements, the role of social media in identity formation, and changing relationship dynamics—the study demonstrates the continued relevance of the play in today’s world. Overall, the research shows that The Way of the World is not just a satire of Restoration society but also a timeless exploration of human behaviour, especially regarding power and language. By investigating the interplay between language, gender, and social power, the study adds to current discussions on Restoration comedy and sheds light on how Congreve’s work can be used to understand modern social changes. Ultimately, it argues that The Way of the World goes beyond its historical context to address broader questions of identity, independence, and the performative nature of social and political life.